(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Socio-psychological adaptation is the process of a person’s adaptation to the social environment, its requirements and conditions. This process is closely related to the psychological state of a person, social relationships and personality development. In modern times, the phenomenon of socio-psychological adaptation takes on new forms under the influence of many factors, including technological changes, globalization and the development of social networks.